Fuzzy TOPSIS method for a tourism destination - Genç, T.; Filipe, J. (MCDM methods for business and management, 2020)
In this study, we intended to create a methodology in order to have a Multi Criteria approach for choosing a tourist destination region or place as Multi Criteria Decision Making (MCDM) is widely used to outrank, choose or cluster the alternatives with respect to multiple criteria and, in general, refers to making decisions among multi alternatives in the presence of multiple, usually conflicting criteria. Conflicting criteria often makes the problem difficult to decide and select the best alternative among the possible choices. To do this, we propose a Fuzzy TOPSIS Method to choose a Tourism destination in Portugal.